Kinetic of the gas-phase reactions of OH radicals and Cl atoms with diethyl ethylphosphonate and triethyl phosphate. (February 2016) - Laversin, H.; El Masri, A.; Al Rashidi, M.; Roth, E.; Chakir, A.
Abstract: In this paper, the relative-rate technique has been used to obtain rate coefficients for the reaction of two organophosphorus compounds: Triethyl phosphate (TEP) and Diethyl ethylphosphonate (DEEP) with OH radicals and Cl atoms at atmospheric pressure and at different temperatures. The calculated rate constants were fitted to the Arrhenius expression over the temperature range 298–352 K. The following expressions (in cm 3  molecule −1  s −1 ) were obtained for the reactions of OH and CL with DEEP and TEP: kOH+DEEP  = (7.84 ± 0.65) × 10 −14 exp((1866 ± 824)/T), kOH+TEP  = (6.54 ± 0.42) × 10 −14 exp((1897 ± 626)/T), kCl+DEEP  = (5.27 ± 0.80) × 10 −11 exp(765 ± 140/T) and kCl+TEP  = (5.23 ± 0.80) × 10 −11 exp(736 ± 110/T). These results show that the reaction of the studied compounds with Cl atoms proceeds more rapidly than that with OH radicals. The related tropospheric lifetimes suggest that once emitted into the atmosphere, TEP and DEEP can be removed within a few hours in areas close to their emission sources. TEP and DEEP are principally removed by OH radicals. However, in coastal areas where the Cl atoms' concentration is higher, TEP and DEEP removal by reaction with Cl atoms could be a competitive process. Graphical abstract: Highlights: This work provides the kinetic reaction of tow organophosphorus compounds with Cl and OH radicals. Studies were carried out over the temperature ranges 298–333 K. Results are compared to those found in literature, reactivity trends are discussed. Effects of temperature and structure and the atmospheric implications are discussed.